ANALYSIS OF APBD SILPA AND CASH FLOW IN THE USE OFCAPITAL EXPENDITURE IN THE DISTRICT GOVERNMENT OF KARO - Oktarini Khamilah Siregar (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
This study focused to determine the contribution SILPA and Cash Flow in the use of the Capital Expenditure in Karo regency government . Samples ares Regional Treasurer (BUD) Karo form of Local Government Financial Statements from 2010 to 2015. The research approach is descriptive research approach by conducting analysis of Contributions . The results of this study indicate that the Revenue Funding is SiLPAwhich has a small contribution to the funding of the Capital Expenditure. While cash flow has Immense Contributions in funding the Capital Expenditure by percentage consistently 100%.